The effect of financial stability, financial targets and rationalization on financial statements fraud - Meihendri; Yunilma; Dandes Rifa; Nurhuda; Irda; Siti Maharani Tasrif (Journal of Contemporary Accounting, 2022)
This study aims to empirically investigate the impact of financial stability, financial targets, and rationalization on instances of financial statement fraud in State-Owned Enterprises operating in the financial services and insurance sector listed on the Indonesia Stock Exchange from 2016 to 2021. The research is motivated by alleged incidents of financial statement manipulation, particularly the practice of window dressing, observed in various financial corporations during 2015 and 2016. The study utilizes secondary data collected from a sample of 14 companies observed over a six-year timeframe. The sample selection employed a purposive sampling technique, and data analysis involved conducting multiple linear regression analysis using the SPSS version 25 software. The findings indicate that financial targets and rationalization have a significant impact on instances of financial statement fraud, while financial stability does not demonstrate a comparable influence.